Counter-Reformation Sanctity in Global and Material Perspective (New York, USA)
1 online resource (216)
Keywords: This book explores the making of saints' cults in the early modern world from an interdisciplinary perspective, considering the entangled roles of materiality and globalization processes. It brings together work across diverse media, objects, and materials as well as communities, cultures, and geographies to reframe a more synoptic, materials-centric, and comparative history of the making and remaking of saints' cults, with a special focus on the long Counter-Reformation. The contributions engage with dynamics of local and universal and draw attention to the vital role of textual, visual, and material hagiographies in the creation and promotion of saints' and would-be saints' cults. The book fosters novel conceptualizations and cross-pollination of ideas across traditions, regions, and disciplines and expands hagiography's horizons by reconsidering canonical saintly figures and reframing lesser-known cults of saints and would-be saints. The bookwill be of interest to scholars of religious and early modern history as well as art history and visual and material studies.